Quality management in Malaysian public health care - Abd. Manaf, Noor Hazilah (Emerald Management Review, 2005)
Purpose – The main aim of the study is to provide an empirical analysis of quality management practice among Malaysian Ministry of Health hospital employees, ranging from medical specialists to health attendants.